Stability And Growth Of It-Based Companies: A Case Of Rania Resources Sdn Bhd - Shahadan Man
Rania Resources Sdn. Bhd. was established on May 27th, 2003. According to the founder, En Muhammad Najib Bin Abdullah, he wanted the company to be one of the top Bumiputera companies. He dreams that the company will continue to grow and be well respected by practising good work culture with integrity. However, in 2016, the company experienced a continuous downtrend in revenue, so much so that the Founder or CEO instructed a thorough diagnostic analysis to be carried out to stop the trend and achieve a turnaround as quickly as possible. The diagnostic analysis was then undertaken, where issues were diagnosed, and solutions were derived through a case study and applied research perspective. The main objective is to ensure that the company improves and stops the downturn trend, and stabilizes the company and make sure that the company continues to grow in the future. The overall issues were categorised into five different cases, and solved one at a time in the five designated trimesters adopting the applied research principles. The five cases covered five different functional areas in management namely general management, finance, marketing, operations, and strategic management. Data were gathered, appropriate analytical tools were applied to the corresponding functional cases, and the resulting solution recommended for implementation for each of them. Each of the case is supported by appropriate theories and relevant analysis tools that were tested and applied, culminating in the findings and recommendations that are expected to help the company's turnaround. This study is different from the others because it takes into account the overall Company’s operations. The five diagnostic areas are presented in this thesis, and they make up the five cases that are analysed in detail. Briefly, the outcome of the diagnostic analysis is that the company is expected (based on the five diagnostic analyses) to achieve the turnaround in 1 to 2 years through improvements and changes in the areas of management or human resources, finance, marketing, operations, and strategic management. In essence, these analyses are carried out to identify critical problems in all five (5) areas and provide possible solutions or improvements to be implemented by the company.